Use of emergency services in Bogotá, Colombia: An analysis from the triage - Rodríguez-Páez, Fredy Guillermo; Jiménez-Barbosa, Wilson Giovanni; Palencia-Sánchez, Francisco (Universidad y Salud, 2018)
Introduction: Emergency services are critical points for the quality of care. Understanding the reasons for their use contributes to the improvement of health systems. Objective: To describe the characteristics of members of the contributory regime who used emergency services in three level III hospitals of complexity in Bogotá, as well as the diagnostic impressions and chronological distribution of the demand, according to the data obtained at the time of being classified in the triage. Materials and methods: A cross-sectional study was conducted based on triage records from October 1, 2012 to March 31, 2013. Results: A third of the records were classified as non-urgent medical consultation. Monday had the greatest number of attentions. Emergencies had daytime behavior. Variables such as: female sex, membership status as a contributor to the health system and age to work were associated with differences in the classification of triage at the time of demand for emergencies. Conclusion: The use of the emergency services is influenced by the relation between: demographic characteristics, condition of affiliation to the health system and classification of the triage.